(untitled) (Ágora de Heterodoxias, 2025)
This article, which is fundamentally an essay methodologically sustained by conceptual analysis and deductive reasoning, complemented by analogy and bibliographic review, emphasizes the importance of spelling and handwriting in veterinary medicine, intrinsically linking them with ethics, professional responsibility, and the animal owner’s right to. Handwriting, as the correct formation of written characters, and spelling, as a system of linguistic norms, are essential for effective communication and a strong professional image. Clarity in the "medical handwriting" of clinical records and prescriptions is crucial for patient safety and for ensuring the proper understanding of instructions. Although poor handwriting is common, its associated erros - or “blunders” - have ethical implications, as they may violate principles such as beneficence, non-maleficence, and client autonomy. They also carry legal consequences related to negligence, according to Venezuelan legislation. Jurisprudence concerning legal professionals’ writing and the doctrine of inexcusable error are applied by analogy. The article concludes by stressing the urgent need to strengthen training in written communication within veterinary schools and to raise awareness of the importance of legibility. This will support an ethical, responsible, and rights-conscious professional practice, safeguarding the animal owner’s right to information and preventing harmful communication errors